Critical success factors of online music streaming services - a case study of applying the fuzzy cognitive maps method. (2016) - Maftei, Vlad Adrian; Gerogiannis, Vassilis C.; Papageorgiou, Elpiniki I.
The business model of online music streaming allows customers to listen to music on their preferred devices without owning any digital music files. The aim of this paper is to identify which are the critical success factors (CSFs) of online music streaming services, what are the relationships between them and at what level the CSFs influence the business overall success. To achieve this aim, a case-study was applied that utilised the fuzzy cognitive maps (FCMs) method. FCMs offer a soft computing tool capable of capturing human knowledge and behaviour of complex problems in uncertain environments. As a case-study to apply the FCM method we selected Bandcamp, a music streaming service that allows users to stream full music albums for free and purchase music in digital/physical format right from the artist's web page. Bandcamp puts a different spin on the streaming music business model. It is an online music store, a streaming service and an artist promotion platform, all at the same time. The research findings suggest that the core CSFs of online music streaming are free music streaming, the ability to purchase digital and physical format music, the lack of advertisements and the satisfaction of supporting one's favourite artists.